Investment Interest with Capital Market Education as Moderator - Fatimah, Fatimah; Nurkhin, Ahmad (Economic Education Analysis Journal, 2021)
This study was to determine the role of investment knowledge and financial literacy in mediating the effect of capital market education on investment interest. This study used a quantitative approach and students of the Faculty of Economics enrolled in the Investment Gallery 2018 & 2019 as populations. The samples used 142 students. The research used simple random sampling. Methods of data collection used questionnaire. Data analysis techniques used descriptive analysis, path analysis, and multiple tests. The results of descriptive analysis showed that investment interest was in very high category then capital market education, investment knowledge, and financial literacy were included in the good category. Capital market education and investment knowledge had a significant positive effect on investment interests respectively by 0.262 and 0.561. Financial literacy had no effect on investment interest. Capital market education had a significant positive effect on investment knowledge 0.601 and financial literacy 0.531. Investment knowledge could mediate the effect capital market education on investment interest. Financial literacy could not mediate the effect capital market education on investment interest. The suggestion is, the implementation of the capital market education program should be evaluated and improved so students can increase investment knowledge, financial literacy, and investment interests.